Effects of Resistance and Combined training on Vascular Function in Type 2 Diabetes: A Systematic Review of Randomized Controlled Trials (The Review of Diabetic Studies, 2019)
BACKGROUND: Cardiovascular disease (CVD) is the main cause of mortality in type 2 diabetes (T2D). Exercise can reduce the risk factors associated with CVD in T2D patients. However, research evaluating its beneficial effects in these patients has used different measurement protocols and types of exercise, complicating comparison. AIM: To assess the effects of resistance training (RT) and combined training (CT) on the vascular function of T2D patients. METHODS: A database search (MEDLINE, Scopus, and Web of Science) was performed to identify relevant articles that were published up to August 2017. Only original studies evaluating the effects of RT or CT interventions on vascular function in T2D patients were included. The articles were reviewed independently by at least three reviewers. The Cochrane guidelines were used to assess the methodological quality of the studies. Fourteen studies were finally included. Two studies only used RT and twelve studies used CT as intervention strategy. RESULTS and CONCLUSIONS: The results show that resistance training is a useful means for primary treatment of vascular diseases and maintenance of vascular function in T2D patients. However, more studies are necessary to gain full knowledge of the beneficial effects and to identify tailored exercise plans to optimize these benefits. The information provided in this review may help to improve current treatment of vascular diseases in T2D patients and to design future studies.